Moral Hazard and Less Invasive Medical Treatment for Coronary Artery Disease: The Case of Cigarette Smoking - Jesse Margolis; Jason Hockenberry; Michael Grossman; Shin-Yi Chou (Institute for the Study of Labor (IZA), 2014)
Comparisons of the effectiveness of two common procedures for Coronary Artery Disease: Percutaneous Coronary Intervention (PCI) and Coronary Artery Bypass Graft (CABG). Evidence indicates that CABG the more invasive procedure leads to superior long term outcomes for otherwise similar patients, though there is little consensus as to why. In this article, we propose a novel explanation: patient offsetting behavior. We hypothesize that patients who undergo the more invasive procedure, CABG, are more likely to improve their behavior eating, exercise, smoking, and drinking in a way that increases longevity. To test our hypothesis, we use Medicare records linked to the National Health Interview Survey to study one such behavior: smoking. We find that CABG patients are 12 percentage points more likely to quit smoking in the one-year period immediately surrounding their procedure than PCI patients, a result that is robust to alternative specifications.
Keywords: I10; I12; 330; coronary artery disease; moral hazard; smoking